TINJAUAN TENTANG PEMILIHAN UMUM DI MA'HAD AL-ZAYTUN BERDASARKAN PASAL 3 UNDANG-UNDANG NOMOR 7 TAHUN 2017 DAN SIYASAH DUSTURIYAH - Nanang Suryana; Abdur Rahim (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
This research is grounded in the understanding that general elections constitute a primary constitutional instrument for realizing popular sovereignty while also serving as a means of continuous political education. Law Number 7 of 2017 affirms the principles of direct, general, free, secret, honest, and fair elections as normative standards for electoral administration, which are also relevant to be adapted within educational settings. Ma’had Al-Zaytun, as an Islamic educational institution, integrates constitutional, democratic, and Islamic values through internal electoral practices that are educational and participatory in nature. These practices not only reflect the implementation of national electoral principles but also embody the principles of Siyasah Dusturiyah, such as shura (consultation), justice, trustworthiness, and public welfare (maslahah). The objective of this study is to examine general elections at Ma’had Al-Zaytun based on Article 3 of Law Number 7 of 2017 and the principles of Siyasah Dusturiyah. This study employs a normative legal approach, or library research. The data consist of primary sources, namely Article 3 of Law Number 7 of 2017, the book Ilmu Hukum dalam Simpul Siyasah Dusturiyah (Reflections on the Theory and Practice of Constitutional Law in Indonesia) by Lubis, and Al-Zaytun: Sumber Inspirasi by Drs. Ch. Robin Simanullang, supported by secondary sources such as relevant journals, books, and scholarly articles. Data were collected through finding, organizing, editing techniques, and then analyzed using content analysis. To ensure data validity, triangulation, member checking, expert judgment were applied. The findings of this study are as follows: (1) General elections at Ma’had Al-Zaytun are conducted in contextual accordance with Article 3 of Law Number 7 of 2017. The application of the principles of direct, general, free, secret, honest, and fair elections, along with the principles of orderliness, transparency, effectiveness, and efficiency, demonstrates the adaptation of national electoral norms within an educational environment without diminishing the substance of democracy. A transparent and participatory process provides social legitimacy and functions as a medium for political and civic education for students. (2) General elections at Ma’had Al-Zaytun are consistent with the principles of Siyasah Dusturiyah, particularly shura, justice, trustworthiness, and the legitimacy of authority. Elections are understood as an ethical constitutional mechanism aimed at achieving the common good, rather than merely an administrative procedure. The internalization of these values fosters legal awareness, ethical leadership, and moral responsibility, and reflects the integration of Islamic values with the national legal system.